ANALISIS PENANDA DAN PETANDA DALAM LAGU MELAYU SAMBAS KARYA BULYAN MUSTHAFA (KAJIAN SEMIOTIKA) - Nurhidayah, Mareta; Sulissusiawan, Ahadi; Sanulita, Henny; Simanjuntak, Hotma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study discusses the analysis of semiotics in the lyrics of the Malay song Sambas by Bulyan Musthafa. This study aims to analyze the signifier and signified contained in the lyrics of the Malay song Sambas by Bulyan Musthafa. The research method used in this study is a qualitative descriptive research method. The data source in this research is the song lyrics by Bulyan Musthafa which consist of two albums Melayu Sambas and Pop Melayu Sambas which are available on VCD and YouTube. The data of this study are in the form of words and sentences contained in the Malay song Sambas by Bulyan Musthafa, signifier and signified data will be analyzed based on color, background setting, players and movement. The data collection technique carried out in this study is in the form of documentary techniques. The results of the study show that in the research data are found seventy-five song lyrics that can be used as data and analyzed based on signifier and signified.